Porous alumina powder for lithium ion battery, battery structural member, battery and electric equipment

By using porous alumina powder with a low specific surface area and moderate pore size, the problem of difficulty in maintaining the electrolyte of lithium-ion battery is solved, and the cycle stability and service life of the battery are improved.

CN119560729APending Publication Date: 2025-03-04SUZHOU GINET NEW MATERIAL TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411811823.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The electrolyte is difficult to maintain during the circulation of existing lithium-ion batteries, resulting in limited lithium-ion transmission, increasing internal resistance, and affecting battery capacity and cycling performance.

Method used

Porous alumina powder with a low specific surface area and moderate pore size is used for the separator or pole sheet coating of lithium-ion batteries to improve the wetting and liquid retention performance of the electrolyte and provide more ion transport channels.

Benefits of technology

It improves the cycle stability and service life of the battery, and enhances the performance of the battery under high-rate charging and discharging and low temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560729A_ABST
    Figure CN119560729A_ABST
Patent Text Reader

Abstract

The invention provides porous aluminum oxide for a lithium ion battery, a battery component, a battery and electric equipment, and relates to the technical field of battery materials, the pore size of particles in porous aluminum oxide powder is 16-50nm, the BET specific surface area is not more than 25m < 2 > / g, the crystal forms of the particles comprise 30-60% of theta phase, 0-50% of delta phase and 0-50% of alpha phase, the alpha phase is 0-50% of the theta phase, the beta phase is 0-50% of the beta phase, and the beta phase is 0-50% of the alpha phase. And the ratio of the alpha phase is 10%-50%. The invention further provides a battery component, a battery and electric equipment based on the porous aluminum oxide. The porous alumina powder provided by the invention has a relatively low specific surface area, relatively low activity and a reasonable pore channel structure, and is beneficial to improving the thermal stability of a diaphragm and the affinity and wettability of the diaphragm to an electrolyte when being applied to a diaphragm coating of a lithium ion battery, improving the liquid retention level and prolonging the service life of the diaphragm. And more ion transmission channels can be provided for ion conduction, so that the cycling stability of the battery is improved, and the service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery materials, and in particular to porous alumina powder, battery structural parts, batteries and electrical equipment for lithium-ion batteries. Background Art

[0002] The electrolyte is one of the most important components of lithium-ion batteries and is mainly responsible for ion transport. However, in practical applications, it is difficult to avoid decomposition and oxidation of the electrolyte during the cycle. As the electrolyte decreases throughout the battery life cycle, it will limit the transmission of lithium ions between the positive and negative electrodes, increase the internal resistance of the battery, and directly affect the battery's capacity, cycle performance, etc., greatly affecting the battery's electrochemical performance. The attenuation of lithium-ion battery performance is closely related to the significant reduction of electrolyte. How to alleviate this challenge is a key issue in contemporary battery research.

[0003] As an inorganic material with electrochemical and chemical stability, porous alumina can better play the role of accelerating electrolyte infiltration and absorption and improving electrolyte retention performance. When porous alumina is used to enhance electrolyte infiltration and retention, it is generally applied to the diaphragm or pole piece. The coating formed by porous alumina can absorb and retain electrolyte in the early stage of battery operation, and release electrolyte in the middle and late stages of battery operation, thereby replenishing the electrolyte actually needed for the electrochemical reaction and improving the battery cycle life.

[0004] In addition, the coating material containing porous alumina can replenish the electrolyte at the electrode interface under extreme working conditions, such as when the electrolyte on the electrode surface is rapidly consumed during high-rate charge and discharge, or when the flow of the electrolyte is restricted under low-temperature conditions, thereby achieving improved rate performance and low-temperature performance.

[0005] When preparing a coating containing porous alumina, on the one hand, in order to improve the uniformity of the distribution of porous alumina in the coating slurry, a dispersant is usually added to the slurry; on the other hand, after the coating is completed, the coating needs to be dried to remove the solvent or moisture contained in the coating and the porous alumina. However, the addition of the dispersant may cause the pores on the surface of the porous alumina to become clogged, thereby affecting its absorption performance of the electrolyte; and if the surface pore size is reduced to avoid clogging, the lithium ion transmission performance may be reduced. In addition, the pore size and pore structure will ultimately affect the specific surface area of ​​the porous alumina. When the specific surface area is too large due to the reduction in pore size, the porous alumina will easily absorb moisture and solvents, making it difficult to dry, or the drying time will be prolonged, reducing production efficiency.

[0006] Therefore, there is an urgent need to provide a porous alumina particle that can take into account both the wetting and absorption performance of the electrolyte and the lithium ion transmission performance of the porous alumina particles in the diaphragm or electrode coating, thereby improving the battery cycle stability and extending the battery life. Summary of the invention

[0007] The purpose of the present invention is to provide a porous alumina powder for lithium-ion batteries. The porous alumina powder provided in the present application has a low specific surface area, low activity and a reasonable pore structure. When applied to the diaphragm coating of lithium-ion batteries, it is beneficial to improve the thermal stability of the diaphragm and the affinity and wettability to the electrolyte, improve the liquid retention level, and it can provide more ion transmission channels for ion conduction, thereby improving the battery cycle stability and extending the battery life.

[0008] Another object of the present invention is to provide a battery structure.

[0009] Another object of the present invention is to provide a battery.

[0010] Another object of the present invention is to provide an electrical device.

[0011] In a first aspect, the present application provides a porous alumina powder for lithium-ion batteries, wherein each particle in the porous alumina powder comprises a plurality of pores, wherein the pore size is 16-50 nm, and the specific surface area of ​​the porous alumina powder is not more than 25 m 2 / g, the crystal forms of the particles include θ phase, δ phase and α phase, wherein the θ phase accounts for 30%-60%, the δ phase accounts for 0-50%, and the α phase accounts for 10%-50%.

[0012] Furthermore, in some embodiments of the present application, in the porous alumina powder, the pore volume of the particles is 0.01-0.07 cm 3 / g.

[0013] Furthermore, in some embodiments of the present application, in the porous alumina powder, the proportion of each crystal form is further preferably 46%-56% for the θ phase, 0-45% for the δ phase, and 12%-46% for the α phase.

[0014] Furthermore, in some embodiments of the present application, in the porous alumina powder, the apparent density of the particles is 2.3-3.4 g / cm 3 .

[0015] Furthermore, in some embodiments of the present application, the specific surface area of ​​the porous alumina powder is no more than 22 m 2 / g, and not less than 10m 2 / g.

[0016] The porous alumina powder is of an orthorhombic structure, and the porous alumina particles are mainly single crystal particles, and the size of the single crystal particles is 0.2-3 μm.

[0017] Further, in some embodiments of the present application, the pore volume is 0.01-0.05cm 3 / g.

[0018] Furthermore, in some embodiments of the present application, the porous alumina powder is directly prepared without compounding multiple porous alumina powders.

[0019] In a second aspect, the present application further provides a battery structural component, characterized in that the battery structural component comprises the porous alumina described in the first aspect.

[0020] Furthermore, in some embodiments of the present application, the battery structural component is a battery separator, which includes a substrate and a coating formed on at least one side of the substrate, wherein the porous alumina is distributed in the coating; and the liquid absorption performance of the battery separator is not less than 0.8 mL / g.

[0021] In a third aspect, the present application further provides a lithium-ion battery, comprising the battery structure described in the second aspect.

[0022] In a fourth aspect, the present application also provides an electrical device, comprising the battery described in the third aspect.

[0023] The embodiment of the present application provides a porous alumina, a battery component, a battery, and an electrical device containing the battery. The porous alumina powder is an orthorhombic structure, the three crystal axes are perpendicular to each other but the lengths are different, and the shape is a columnar or plate-like structure similar to a rectangular parallelepiped. The porous alumina particles contained in the porous alumina powder are mainly single crystal particles, and the crystal forms of the particles include θ phase, δ phase and α phase, wherein the θ phase accounts for 30%-60%, the δ phase accounts for 0-50%, and the α phase accounts for 10%-50%. Compared with highly active alumina powder, the porous alumina powder provided in the present application has a lower specific surface area and weaker adsorption to water or organic solvents, which avoids the difficulty in reducing the water content in the porous alumina powder, or the long time it takes to reduce it to the required water content, or the electrolyte consumption and battery performance degradation caused by the decrease in stability due to water absorption during use. In addition, the pore size of the porous alumina particles is no more than 50 nm, thereby avoiding the clogging of the porous alumina pores by the dispersant in the diaphragm coating slurry, thereby affecting the lithium ion transmission channel and the liquid absorption performance of the porous alumina; at the same time, it is also necessary to ensure that the pore size of the porous alumina particles is not less than 16 nm, which is larger than the size of the solvated lithium ions, so as to ensure the smooth transmission of lithium ions and improve the ionic conductivity.

[0024] The porous alumina powder provided in the present application has a low specific surface area, low activity and a reasonable pore structure. When applied to the diaphragm coating of lithium-ion batteries, it is beneficial to improve the thermal stability of the diaphragm and the affinity and wettability to the electrolyte, improve the liquid retention level, and it can provide more ion transmission channels for ion conduction, thereby improving the battery cycle stability and extending the battery life. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The XRD spectrum of porous alumina provided in Example 4 of the present application. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Alumina is an inorganic particle commonly used in the field of secondary batteries due to its excellent chemical stability, thermal stability, corrosion resistance and high hardness. It is often found in the coating of battery diaphragms, electrode material coatings and other battery components that are in direct contact with the electrolyte. The inventor found that when porous alumina particles are applied to battery components, especially when used as a diaphragm coating, their porous structure is conducive to improving the wetting and adsorption properties of the electrolyte and increasing the liquid retention. At the same time, the porous structure is also conducive to providing a channel for lithium ion transmission to ensure ionic conductivity. However, in the preparation process of the coating containing porous alumina particles, it is usually necessary to add a dispersant to improve the uniformity of the dispersion of alumina particles in the slurry and finally in the coating. During the slurry dispersion process, the introduction of the dispersant may cause the pores on the surface of the porous alumina particles to be blocked, causing lithium ions to shuttle poorly and affect the battery cycle performance. It can be seen that the pore size of the porous alumina needs to take into account the passage of lithium ions and avoid the blockage of other substances such as dispersants. At the same time, the pore size, pore volume, and specific surface area jointly determine the electrolyte adsorption performance of porous alumina. The inventors found that by controlling the internal pore structure of porous alumina, and then controlling its pore size, pore volume, and specific surface area, it is possible to take into account both the lithium ion transmission performance and the electrolyte adsorption performance, and at the same time avoid the problems of porous materials being difficult to dry or easy to absorb water caused by excessive specific surface area. On this basis, the applicant proposed a porous alumina powder in this application, which has a specific particle crystal phase structure composition, and the pore size can ensure the transmission of lithium ions and avoid the blockage of substances such as dispersants. The pore volume can ensure the electrolyte adsorption amount of porous alumina, and the lower specific surface area can avoid the porous alumina from absorbing too much water and being difficult to dry. When it is applied to the diaphragm coating, while improving the mechanical strength and thermal stability of the diaphragm, it is beneficial to the absorption, storage, and increase of ion transmission channels of the electrolyte.

[0028] The solutions provided in this application are as follows:

[0029] The crystal forms of the alumina particles in the porous alumina powder include θ phase, δ phase and α phase, wherein the θ phase accounts for 30%-60%, the δ phase accounts for 0-50%, and the α phase accounts for 10%-50%; wherein the proportions of the θ phase, the δ phase and the α phase are obtained by X-ray diffractometer testing.

[0030] Preferably, the θ phase is 46%-56%, the δ phase is 0-45%, and the α phase is 12%-46%.

[0031] In the present application, the porous alumina powder comprises a plurality of pores on the porous alumina particles, and the specific surface area of ​​the porous alumina powder does not exceed 25 m 2 / g, the pore size is 16-50nm, and the pore volume is 0.01-0.07cm 3 / g.

[0032] Specifically, the specific surface area of ​​the porous alumina powder is further preferably not more than 22 m 2 / g, and not less than 15m 2 / g.

[0033] During the storage and application of alumina powder, it is inevitable that it will come into contact with water molecules for a long time, and a slow hydration reaction will occur, causing it to generate high-viscosity and highly active hydrated alumina. Therefore, the low and stable water content in the alumina powder is critical for its application in batteries. In the process of applying porous alumina powder to battery diaphragms and performing slurry coating, water is usually used as the slurry solvent, and after the coating is completed, the coating needs to be baked and dried. Once the specific surface area of ​​the porous alumina is too large, it is not easy to dry it, or a longer drying time is required. Therefore, the specific surface area of ​​the porous alumina used in the battery diaphragm coating should not be too large to avoid it being easy to absorb moisture, difficult to dry, and affecting the battery performance. In the porous alumina powder provided in the present application, the specific surface area of ​​the alumina particles is relatively low, compared with the ultra-high specific surface area (such as 150m 2 / g or more), it is easier to form aluminum oxide powder with lower water content during the preparation process, and the water content stability in the aluminum oxide powder during storage is also better, and it is not easy to have defects such as agglomeration and adhesion. At the same time, the aluminum oxide powder provided by the present application still has a certain specific surface area to ensure space for storing electrolyte, improve the electrolyte retention capacity and ion transmission channel.

[0034] Specifically, the pore size of the porous alumina particles is further preferably 16-50 nm, and the pore volume is further preferably 0.01-0.05 cm 3 / g.

[0035] The pore structure of porous alumina particles can improve the infiltration and liquid retention capacity of electrolytes. In the electrolyte, the size of solvated lithium ions is 5nm. Therefore, in order to improve the ionic conductivity of lithium batteries, a large number of ion channels > 5nm need to be provided. But at the same time, when the pore size is too large, the dispersant in the diaphragm coating slurry will enter the pores and occupy the pores, thereby affecting the transmission of lithium ions. Therefore, it is also necessary to control the size of the pore size to be smaller than the molecular size of the dispersant, not exceeding 50nm. Among them, the diameter of the dispersed particles is between 50-100nm. In the solution system, when the dispersant is water or other liquids, if a solution state is formed, the diameter of the solute particles in the size of the dispersion is usually less than 1nm; if a colloid is formed, the diameter of the dispersed particles is between 1nm and 100nm; if a turbid liquid is formed, the diameter of the dispersed particles is greater than 100nm. The molecular weight of the dispersant used in the lithium battery industry is about 7000-50000, which generally forms a colloid state, and the diameter of the dispersed particles is between 50-100nm. The test method is dynamic light scattering (DLS). The specific principle is that the particles in the colloid will perform Brownian motion, and this irregular motion causes the intensity of the scattered light to fluctuate. By detecting the fluctuation of this light intensity and using relevant theoretical models and calculation formulas, the particle size and its distribution can be obtained. Large particles move slowly, causing the intensity of the scattered light spot to fluctuate slowly; small particles move quickly, causing the density of the scattered light spot to fluctuate rapidly. According to the Stokes-Einstein equation, the Brownian motion speed of the particle can be related to the particle size, and then the particle size can be calculated.

[0036] Porous alumina particles with the above-mentioned pore size can not only increase the infiltration speed of the electrolyte, but also realize the rapid shuttling of lithium ions, and at the same time block the dispersant from occupying the pores, thereby making full use of the pore structure of the porous alumina particles to improve the overall electrochemical performance of the battery.

[0037] In the porous alumina powder provided in the present application, the apparent density of the particles is 2.4-3.2 g / cm 3 The porous alumina powder has an orthorhombic crystal structure, and the angles between the faces conform to the characteristic angles of the orthorhombic crystal system, that is, the axial angle α=β=γ=90°, the axial unit a≠b≠c, with obvious edges and planes, presenting a relatively regular polyhedron shape.

[0038] The porous alumina particles are mainly single crystal particles, and the size of the single crystal particles is 0.2-3 μm.

[0039] The porous alumina powder provided in the present application is directly prepared without compounding multiple porous alumina powders. That is, the porous alumina powder provided in the present application is not formed by screening, grading, or compounding, but the morphology of the product directly prepared from the raw materials is as follows.

[0040] In this regard, in order for those skilled in the art to better understand and implement the present application, a preparation method for the porous alumina powder is also provided below.

[0041] Step (1): Place aluminum hydroxide, a dispersant, seed crystals and pure water into a vertical stirred mill and grind for 1-5 hours to obtain aluminum hydroxide slurry.

[0042] Step (2): put aluminum hydroxide slurry into a hydrothermal reactor, control the reaction temperature to 180°C-200°C, the reaction time to 10-50h, and the pressure to 1.5-3MPa to obtain a porous alumina precursor slurry.

[0043] Step (3): The porous alumina precursor slurry is acidified to a pH value of 7-8.5.

[0044] Step (4): filter-press and wash the porous alumina precursor slurry to obtain a porous alumina precursor filter cake; the filter cake has a water content of 70% and an electrical conductivity of ≤60 μs / cm.

[0045] Step (5): subjecting the porous alumina precursor filter cake to microwave infrared drying, with the microwave temperature zone controlled at 90-110°C and the infrared temperature zone controlled at 120°C-130°C, to obtain a porous alumina precursor powder with a water content of ≤0.3%.

[0046] Step (6): ultrafinely break up the porous alumina precursor powder, with a crushing pressure of 0.2-0.6 MPa and a classifying wheel frequency of 10-90 Hz, to obtain a monodisperse porous alumina precursor powder.

[0047] Step (7): calcining the porous alumina precursor powder, loading the powder into a corundum sagger, with the sagger loading being >90%; heating the calcining furnace at a rate of 1-10°C / min, holding the temperature at 600-1200°C, and holding the temperature for 0.5-5h to obtain porous alumina agglomerates.

[0048] Step (8): Ultrafinely breaking up the porous alumina agglomerates to obtain a porous alumina finished product.

[0049] By setting different insulation temperatures in step (7), porous alumina with different crystal forms and different pore sizes can be obtained; preferably, the calcination insulation temperature is 1000-1100°C, which can obtain porous alumina with a pore size of 16-50nm.

[0050] In step (1), the mass ratio of aluminum hydroxide, dispersant, seed crystal and pure water is 1:0.0005-0.005:0.0025-0.005:2.5; wherein the dispersant can be acrylate, polyvinylidene fluoride, polyvinyl pyrrolidone, and the seed crystal is ≤100nm aluminum oxide.

[0051] In step (3), the specific method of adjusting the acid is to prepare a 10 mol / L solution of oxalic acid, add the solution into the reaction solution, stir and neutralize to pH = 7-8.5.

[0052] In step (7), the calcination of the porous alumina precursor powder can be carried out in stages.

[0053] The porous alumina precursor lattice contains a large amount of crystalline water. With the control of the calcination furnace temperature, heat energy is transferred from the powder surface to the powder center. The crystalline water on the powder surface overflows first, and the crystalline water in the powder center overflows later. Due to the different overflow orders of the powder crystalline water, the porous alumina has a variety of pore structures, including tunnel holes, worm holes, through holes, and surface depression holes.

[0054] The eight common crystal forms of alumina are α, γ, δ, κ, η, θ, χ and ρ. Except for α-alumina which is a thermodynamically stable phase, the rest are transition phases. At a certain temperature, the transition phase can be converted to α phase and the process is irreversible. α-phase alumina belongs to the corundum structure, which makes its crystal stability much greater than other alumina crystal forms. With the increase of the insulation temperature, the main difference in the crystal structure of transition phase alumina is that the position of aluminum ions has changed under the same arrangement of oxygen ions. The conversion between them does not destroy the morphology of the original crystal particles and the chemical bonds of alumina. During this period, the stacking mode of oxygen ions remains unchanged, and only the local transfer of aluminum ions is a displacement phase change, which will not destroy the original crystal morphology. The process of transition phase alumina transforming into α-alumina is the transition from the transition phase with Fcc (face-centered cubic) structure oxygen ions to the stable phase with Hcp (close-packed hexagonal) structure oxygen ions, and the oxygen ions are rearranged to reconstruct the lattice. Therefore, when porous alumina is in the transition phase, the pore size is controlled by controlling the overflow rate of crystal water by temperature; when porous alumina is in the α phase, the overflow rate of crystal water and the rearrangement of oxygen ions to form holes together affect the pore size of porous alumina.

[0055] In a second aspect, the present application further provides a battery structural component, characterized in that the battery structural component comprises the porous alumina described in the first aspect. Wherein, the battery structural component is a battery separator, and the battery separator comprises a substrate and a coating formed on at least one side of the substrate, wherein the porous alumina is distributed in the coating. The liquid absorption performance of the battery separator is not less than 0.8 mL / g.

[0056] In a third aspect, the present application further provides a battery, comprising the battery structure described in the second aspect.

[0057] In a fourth aspect, the present application further provides an electric device, comprising the battery described in the third aspect. The electric device may be an electric vehicle, an aircraft, an aircraft, a mobile phone, a tablet computer, a handheld game console, a portable digital device (such as a digital camera), a smart home, a smart wearable device (such as a smart bracelet, a smart watch, smart glasses), or any other electric device that can use a lithium-ion battery.

[0058] In order to facilitate those skilled in the art to understand the innovation of the present application, some preferred embodiments are provided below in conjunction with the accompanying drawings to illustrate the above technical solution.

[0059] Example 1

[0060] The present embodiment provides a method for preparing porous alumina powder, comprising the following steps: aluminum hydroxide, dispersant, seed crystals, and pure water are put into a vertical stirred mill according to a mass ratio of 1:0.001:0.003:2.5, wherein the dispersant is polyacrylate and the seed crystals are 80nm alumina, and the mixture is ground for 1 hour to obtain aluminum hydroxide slurry. The aluminum hydroxide slurry is put into a hydrothermal reactor, the reaction temperature is controlled to 200°C, the reaction time is 40h, and the pressure is controlled to 2.8MPa to obtain a porous alumina precursor slurry. The porous alumina precursor slurry is acidified, oxalic acid is prepared into a 10mol / L solution, and the solution is added to the reaction solution and stirred to neutralize it to pH=8. The porous alumina precursor slurry is filter-filtered and washed to obtain a porous alumina precursor filter cake; the filter cake has a water content of 70% and a filter cake conductivity of ≤60μs / cm. The porous alumina precursor filter cake is subjected to microwave infrared drying, the microwave temperature zone is controlled at 90-110°C, and the infrared temperature zone is controlled at 120°C-130°C, to obtain a porous alumina precursor powder with a water content of ≤0.3%. The porous alumina precursor powder is ultrafinely broken up, the crushing pressure is 0.4MPa, and the frequency of the grading wheel is 60Hz, to obtain a monodispersed porous alumina precursor powder. The porous alumina precursor powder is calcined, and the powder is loaded into a corundum sagger, and the sagger loading is >90%; the calcination furnace heating rate is 5°C / min, the insulation temperature is 600°C, and the insulation time is 3h to obtain porous alumina agglomerates. The porous alumina agglomerates are ultrafinely broken up to obtain a porous alumina finished product.

[0061] Example 2

[0062] This embodiment also provides a method for preparing porous alumina powder. Compared with Example 1, the calcination and insulation temperature of the porous alumina precursor powder is 750° C., and the remaining preparation steps are the same as those of Example 1 to obtain porous alumina powder.

[0063] Example 3

[0064] This embodiment also provides a method for preparing porous alumina powder. Compared with Example 1, the calcination and insulation temperature of the porous alumina precursor powder is 900° C., and the remaining preparation steps are the same as those of Example 1 to obtain porous alumina powder.

[0065] Example 4

[0066] This embodiment also provides a method for preparing porous alumina powder. Compared with Example 1, the calcination and insulation temperature of the porous alumina precursor powder is 1000° C., and the remaining preparation steps are the same as those in Example 1 to obtain porous alumina powder.

[0067] Example 5

[0068] This embodiment also provides a method for preparing porous alumina powder. Compared with Example 1, the calcination and insulation temperature of the porous alumina precursor powder is 1100° C., and the remaining preparation steps are the same as those in Example 1 to obtain porous alumina powder.

[0069] Example 6

[0070] This embodiment also provides a method for preparing porous alumina powder. Compared with Example 1, the calcination and insulation temperature of the porous alumina precursor powder is 1200° C., and the remaining preparation steps are the same as those in Example 1 to obtain porous alumina powder.

[0071] Example 7

[0072] This embodiment also provides a method for preparing porous alumina powder. Compared with Example 4, during the calcination of the porous alumina precursor powder, the heating rate of the calcination furnace is 3°C / min, and the remaining preparation steps are the same as those in Example 4 to obtain porous alumina powder.

[0073] Example 8

[0074] This embodiment also provides a method for preparing porous alumina powder. Compared with Example 4, during the calcination of the porous alumina precursor powder, the heating rate of the calcination furnace is 10°C / min, and the remaining preparation steps are the same as those in Example 4 to obtain porous alumina powder.

[0075] test

[0076] 1. Particle size

[0077] The test was carried out using a Mastersizer 3000 laser particle size analyzer.

[0078] 2. Pore volume and specific surface area

[0079] The test was carried out using Micromeritics physical adsorption instrument 3030.

[0080] 3.XRD

[0081] The test was carried out using an X-ray diffractometer.

[0082] 4. Liquid absorption rate

[0083] The coated diaphragm is cut into several rectangles of 20 mm × 50 mm, which are denoted as AT1, AT2, ... and AL1, AL2, ..., and weighed respectively to obtain the diaphragm mass M1;

[0084] The diaphragm is completely immersed in the electrolyte and left for a period of time to ensure that the electrolyte is completely absorbed, and then the coated diaphragm is dried in the shade for 12 to 24 hours; the diaphragm after drying in the shade is weighed to obtain the mass of the diaphragm after soaking M2; the liquid absorption rate of multiple coated diaphragms is calculated, and the average value is taken as the final liquid absorption rate of the coated diaphragm: (M2-M1) / (M1*ρelectrolyte).

[0085] 5. Heat shrinkage

[0086] The traditional oven test method is adopted. Cut 3 square diaphragms with a side length of 100mm. When cutting the diaphragm, one edge should be parallel to the longitudinal edge of the diaphragm, the maximum deviation angle should not exceed 5°, and the longitudinal and transverse markings should be done well. Place the stainless steel plate and two quantitative filter papers in the middle of the oven (near the temperature probe position), and set the oven temperature to 130℃±1℃. After measuring the longitudinal and transverse lengths of the sample in the marked direction, place the diaphragm flat on one of the quantitative filter papers on the stainless steel plate in the middle of the blast thermostat, and stack no more than 10 diaphragms at most. After completion, press it with another quantitative filter paper and place a pressing block in the middle of the filter paper. Close the thermostat door, start counting the time, and keep it at 130℃ for 1h. After the heating is completed, take out the diaphragm, and after the diaphragm returns to room temperature, measure the longitudinal and transverse marking lengths again. Calculate the longitudinal and transverse shrinkage rates of the diaphragm according to the corresponding formulas, and take the average of the three test results as the thermal shrinkage rate of the diaphragm. The calculation formula is: heat shrinkage rate = (size before heating - size after heating) / size before heating × 100%.

[0087] 6. Tensile strength

[0088] The test was conducted using ASTM D882 (Standard Test Method for Tensile Properties of Thin Plastic Sheets).

[0089] 7. Breathability

[0090] The test was performed using the Gurley method.

[0091] 8. Acupuncture intensity

[0092] GB / T 36363-2018 (Polyolefin separators for lithium-ion batteries) was used for testing.

[0093] The porous alumina powders obtained in the above Examples 1-10 were subjected to pore diameter, pore volume, specific surface area, apparent density and XRD tests, and the test results are shown in Table 1.

[0094] Table 1

[0095]

[0096] In Table 1, the indicators of 50 nm pore size / powder and 100 nm pore size / powder are obtained in the following manner: using an NVIDIA Quadro image processor, setting a 50 nm ruler and a 100 nm ruler, adjusting the grayscale of the transmission electron microscope image so that the grayscale of the pixel with the highest grayscale is adjusted to 255, and automatically matching the pixel with a grayscale not higher than 100 in the transmission electron microscope image to calibrate the target.

[0097] It can be seen from Table 1 that as the calcination temperature increases, the crystal form of porous alumina changes from γ phase to mixed phase and finally to α phase, and the pore size gradually increases as the temperature increases. From the apparent density, it can be seen that as the temperature increases, the number of through holes in porous alumina also increases.

[0098] For Example 4 and Examples 7-8, the test results of 50nm pore size / particle powder and 100nm pore size / particle powder show that the powder surface is mostly dense pores with small pore sizes. Although there are large pores, their number is very small, thereby avoiding the clogging of the surface pores by the dispersant as much as possible.

[0099] For Example 4 and Example 7, at the same insulation temperature (1000°C), when the heating rate increases, the porous alumina crystal form also changes accordingly, specifically, the proportion of δ phase gradually increases, the proportion of α phase gradually decreases, and the proportion of θ phase remains basically unchanged. At the same time, the pore volume of porous alumina gradually increases, but the specific surface area and apparent density are relatively stable and change little. The reason for the above changes is: the increase in the heating rate means that the amount of heat absorbed by the system per unit time increases, and the reaction rate accelerates. In the process of faster heating, the crystal transformation process of alumina may not have time to fully proceed, and some crystal forms in the intermediate transition state may not have time to be completely transformed into the most stable α phase. The δ phase is a relatively unstable transition phase, which is easier to generate when the reaction time is insufficient, so the proportion of the δ phase will gradually increase.

[0100] For Example 8, at the same insulation temperature (1000°C), when the heating rate is increased to 10°C / min, the porous alumina crystal form changes significantly, specifically, the δ phase disappears, the proportion of the θ phase and the α phase is significantly reduced, and the proportion of the γ phase increases. When the same insulation temperature is reached at a lower heating rate, the γ phase will not be produced. At the same time, the pore size of the porous alumina is reduced as a whole, which is easy to cause clogging of the dispersant and is not conducive to the smooth transmission of lithium ions. The reason for the above changes is that the increase in the heating rate shortens the time scale of the reaction, and the growth and transformation process of the crystal is restricted. This may cause some crystal forms to be unable to fully form or stably exist, while the new crystal form (γ phase) is generated because it has a relatively low energy barrier under rapid heating conditions. The water molecules wrapped in the intermediate quickly rush out of the lattice without enough time to stay, resulting in a reduction in the overall pore size.

[0101] The following further describes the thermal shrinkage, mechanical strength, liquid absorption, etc. when the porous alumina powder is used as a diaphragm coating.

[0102] Raw materials: porous alumina provided in Examples 4, 5 and 8; purchased boehmite (purchased from Yishitong BG601) as control example 1, and alumina (70W04) purchased from Yujinyi as control example 2.

[0103] The pore size, specific surface area, pore volume and apparent density of the samples of Control Example 1 and Control Example 2 are shown in Table 2; the alumina in Control Example 2 is α-phase alumina.

[0104] Table 2

[0105] serial number Pore ​​diameter / nm <![CDATA[Specific surface area / m 2 / g]]> <![CDATA[Pore volume / cm 3 / g]]> <![CDATA[Apparent density / g / cm 3 > Comparative Example 1 none 8.67 0.0224 3.0773 Comparative Example 2 none 9.32 0.0233 4.027

[0106] Preparation of diaphragm samples:

[0107] PE separator 9μm, Suzhou Jieli New Energy Materials Co., Ltd.;

[0108] Dispersant SF8, Sannopco, Japan;

[0109] Adhesive BM900-B, Japan Zeon;

[0110] Lauryl alcohol polyoxyethylene ether, Nantong Haian Chemical.

[0111] Take 100g of alumina (boehmite) powder and 180g of deionized water, stir and mix for 10min, add 5g of dispersant SF8, stir for 30min, and prepare ceramic slurry.

[0112] The ceramic slurry was coated on the surface of the diaphragm on an online rod coater and dried in a blast oven at 40°C for 10 minutes to obtain a coated diaphragm with a coating thickness of 2 μm.

[0113] Negative electrode coating:

[0114] Take 50g of alumina powder and 100g of deionized water, stir and mix for 10min, add 3g of carbon black, stir for 10min, add 3g of methyl cellulose as a binder, stir for 30min, and prepare ceramic slurry.

[0115] The slurry was evenly scraped on the current collector by a scraper, and dried in a forced air oven at 120° C. for 10 min to obtain an alumina coating coated electrode, and the electrode coating thickness was 35 μm.

[0116] The above-mentioned diaphragm and pole piece are assembled into a lithium battery.

[0117] The thermal shrinkage rate, mechanical strength and air permeability of the diaphragm were tested, and the lithium battery injection volume was tested. The specific composition of the electrolyte is as follows:

[0118] Solvent: DEC:EMC:DMC=1:1:1, the above ratio is mass ratio;

[0119] Lithium salt: LiPF6;

[0120] Additive: FEC;

[0121] The solvent accounts for 85wt%, the lithium salt accounts for 12wt%, and the additive accounts for 3wt%.

[0122] The test results are shown in Table 3.

[0123] Table 3

[0124]

[0125] It can be seen from Table 3 that, compared with Control Examples 1 and 2, when the porous alumina powder provided in Examples 4 and 5 is used as a diaphragm coating, the diaphragm exhibits excellent performance in terms of thermal shrinkage and mechanical strength, and the liquid absorption rate is greater than 0.8 mL / g. Compared with Examples 4 and 5, the porous alumina powder of Example 8 has a smaller overall pore size due to the excessively fast heating rate, and the liquid absorption rate is only 0.62 mL / g. Compared with Control Examples 1 and 2, Examples 4, 5 and 8 have a porous structure, and when air passes through the diaphragm coating layer, it can not only pass through the powder accumulation pores, but also through the porous structure of the powder itself. Therefore, under certain temperature, humidity and pressure conditions, the time required to pass 100 mL of air is shorter, that is, the air permeability value is smaller.

[0126] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A porous alumina powder for lithium ion batteries, characterized in that: The pore size of the particles in the porous alumina powder is 16-50nm, and the specific surface area does not exceed 25m 2 / g, the crystal form of the particles includes θ phase, δ phase and α phase, wherein the θ phase accounts for 30%-60%, the δ phase accounts for 0-50%, the α phase accounts for 10%-50%, and the pore volume is 0.01-0.07cm 3 / g.

2. The porous alumina powder for lithium ion batteries according to claim 1, characterized in that The apparent density of the particles in the porous alumina powder is 2.4-3.2 g / cm 3 .

3. The porous alumina powder for lithium ion batteries according to any one of claims 1 to 2, wherein the specific surface area of ​​the porous alumina powder is not more than 22 m 2 / g, and not less than 10m 2 / g.

4. The porous alumina powder for lithium ion batteries according to any one of claims 1 to 2, wherein the pore volume of the particles in the porous alumina powder is 0.01-0.05 cm 3 / g.

5. The porous alumina powder for lithium ion batteries according to any one of claims 1 to 2, wherein in the crystal form of the particles, the θ phase accounts for 46%-56%, the δ phase accounts for 0-45%, and the α phase accounts for 12%-46%.

6. The porous alumina powder for lithium-ion batteries according to any one of claims 1 to 5, wherein the porous alumina powder is an orthorhombic crystal structure, and the angles between the various faces conform to the characteristic angles of the orthorhombic crystal system, that is, the axial angles α=β=γ=90°, the axial units a≠b≠c, and the powder has obvious edges and planes and is a relatively regular polyhedron shape.

7. The porous alumina powder for lithium ion batteries according to claim 1, characterized in that The porous alumina powder is directly prepared without compounding a variety of porous alumina powders.

8. A battery structural component, characterized in that: The battery structural component comprises the porous alumina according to any one of claims 1 to 7.

9. The battery structure according to claim 8, characterized in that: The battery structural component is a battery separator, which includes a substrate and a coating formed on at least one side of the substrate, wherein the porous alumina is distributed in the coating; and the liquid absorption performance of the battery separator is not less than 0.8 mL / g.

10. A battery, characterized in that: Including the battery structural member described in claims 8-9.

11. An electrical device, characterized in that: Comprising the battery as claimed in claim 10.

Citation Information

Cited By

  • Porous alumina with ultralow magnetic impurity content, preparation method, battery component and battery

    CN121202168A

  • Nano porous alumina, preparation method and application thereof, and lithium ion battery diaphragm

    CN121361814A